2005
DOI: 10.2466/pms.101.3.803-807
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Pain Thresholds Influenced by Sex of Experimenter

Abstract: Thresholds for pressure pain were tested in 64 adult human subjects (age: M=22.0 yr., SD=7.5). The subjects were young adults drawn from a student population. They were divided into two groups of men and two groups of women, with 16 participants in each group. A female experimenter tested one group of men and a male experimenter tested the other group. The women were tested in a similar way by an experimenter of the same sex for one group and the opposite sex for the other group. The two experimenters were dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 10 publications
5
47
2
Order By: Relevance
“…We enrolled only female patients and probands in the study to create a study group as homogenous as possible and to avoid effects influenced by the gender. Moreover, it has been shown that gender of both the experimenter and the subjects has a major impact on the subjective pain thresholds [39]. Nevertheless, using only female subjects might be a limitation of our study.…”
Section: Discussionmentioning
confidence: 97%
“…We enrolled only female patients and probands in the study to create a study group as homogenous as possible and to avoid effects influenced by the gender. Moreover, it has been shown that gender of both the experimenter and the subjects has a major impact on the subjective pain thresholds [39]. Nevertheless, using only female subjects might be a limitation of our study.…”
Section: Discussionmentioning
confidence: 97%
“…For example, women have a higher tendency to seek medical care than men 26 , and patients may report different pain levels based on the gender of the physician evaluating them. 8, 12, 19 We also used only the first pain measurement recorded during an encounter to avoid potential bias introduced by physician-prescribed analgesic treatment, but in most cases, we had limited knowledge concerning the use of over-the-counter pain relievers prior to the encounter. Nevertheless, we believe that working with large-scale human data from a broad population is extremely valuable for corroborating the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of a patient’s mood and lack of personal coping strategies, such as a tendency to catastrophize, have been well-studied. 12, 19, 35 …”
Section: Discussionmentioning
confidence: 99%
“…[14] In case of cross-over studies it is important to maintain the same investigator in all the pain assessments, as the gender and appearance of the investigator can influence the pain rating of the volunteers. [15] The sensitivity of a given experimental model for detecting analgesia is affected by the method used to measure this pain. Hence, good sensitivity of a model is obtained by using a pain assessment method that is reliable in producing data with modest variance (noise).…”
Section: Discussionmentioning
confidence: 99%